GIS-based Spatial Analysis of the Evolution of Residential Developments; A Case-study of Sulaimani city, Iraq - Mohammed, Shaimaa Sarwar; Rasul, Hoshyar Qadir; Mohammed, Hussein Darweesh (Kurdistan Journal of Applied Research, 2024)
This research is aimed at visualizing the historical evolution of residential landuse development of Sulaimani city based on GIS spatial analysis with the input of all of the relevant available data in various formats in order to determine the form of the city according to morphological classifications discussed in the literature of urban planning. Essentially, following the collection of data, processing, review of relevant literature and applied methods, this study draws a timeline for the spatial evolution of the city of Sulaimani in addition to constricting a spatial grid for morphological comparison of different growth stages and analysis on multiple aspects. Moreover, a number of criteria were established to evaluate spatial patterns based on published theories in the field of landuse urban planning. These indicators were formulated in a questionnaire survey and determined the main aspects of the city through visualizing the process of historical evolution up to modern date. Finally, the study presents transformations and addresses current issues, as well as recommends a number of possible solutions for residential landuse development in the city of Sulaimani.